117k views
1 vote
What is the solution to 6(3x +7) = -5(4x -3) - 49 ?​

User Mabg
by
5.2k points

2 Answers

2 votes

Answer:

x = -2

Explanation:

You would first distribute.

6(3x + 7) = -5(4x - 3) - 49 → 18x + 42 = -20x + 15 - 49

We can then calculate difference of 15 and 49.

18x + 42 = -20x + 15 - 49 → 18x + 42 = -20x -34

We can now move the variables to one side of the equation and the numbers on the other side.

18x + 20x + 42 - 42 = -20x + 20x - 34 - 42 → 38x = -76

Then, divide.

38x ÷ 38 = -76 ÷ 38 → x = -2

User Emobe
by
5.1k points
4 votes

Answer:

x = -2

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

6(3x + 7) = -5(4x - 3) - 49

Step 2: Solve for x

  1. Distribute: 18x + 42 = -20x + 15 - 49
  2. Combine like terms: 18x + 42 = -20x - 34
  3. Add 20x on both sides: 38x + 42 = -34
  4. Isolate x term: 38x = -76
  5. Isolate x: x = -2
User Tempus
by
4.2k points